Chromosome numbers of some Asteraceae species from Universitas Indonesia Campus, Depok, Indonesia - ANDI SALAMAH; RIRIN OKTARINA; EKA AYU AMBARWATI; DWI FAUZIYAH PUTRI; ASTARI DWIRANTI; NOVIAR ANDAYANI (Society for Indonesian Biodiversity, 2018)
Salamah A, Oktarina R, Ambarwati EA, Putri DF, Dwiranti A, Andayani N. 2018. Chromosome numbers of some Asteraceae species from Universitas Indonesia Campus, Depok, Indonesia. Biodiversitas 19: 2079-2087.  Asteraceae is the largest plant family, comprising of more than 1,600 genera and 23,000 species with a worldwide distribution. Many species of Asteraceae are found to be very significantly abundant in a range of habitats and are used as sources of medicines, food, forage, and other useful products. Many cytological studies have been carried out on Asteraceae. However, information about the chromosome numbers of Asteraceae in Indonesia is still very limited. In this study, the chromosome numbers of 15 species of Asteraceae found around the Universitas Indonesia campus were counted. For chromosomal preparations, the root/shoot tips were pretreated with 2 mM 8-hydroxyquinoline, stained with aceto-orcein, prepared using the squash method, and then observed with a microscope. Of the 15 species, 12 showed variation in chromosome numbers: Cosmos caudatus, Elephantopus scaber, Tridax procumbens, Mikania micrantha, Sphagneticola trilobata, Ageratum conyzoides, Cyanthillium cinereum, Chromolaena odorata, Synedrella nodiflora, Youngia japonica, Eclipta prostrata, and Porophyllum ruderale. The other three species showed no variation in chromosome number: Emilia sonchifolia (2n=10), Sonchus arvensis (2n=18), and Cosmos sulphureus (2n=24). We also found new variations in chromosome numbers that have not yet been listed in the Index to Plant Chromosome Numbers (IPCN).